2017
DOI: 10.1071/cp17229
|View full text |Cite
|
Sign up to set email alerts
|

Row spacing is more important than seeding rate for increasing Rhodes grass (Chloris gayana) control and grain yield in soybean (Glycine max)

Abstract: In Australia, soybean (Glycine max (L.) Merr.) is planted at a low density in wide rows, and weeds substantially reduce yield because of opportunities for their growth in the wide rows. Field studies were conducted over 2 years at the University of Queensland farm, Gatton, Australia, to assess the effect of row spacing and seeding rate on the competitiveness of soybeans with a model weed, Rhodes grass (Chloris gayana Kunth). The experiment was conducted in a split-split plot design, replicated three times. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…This range of GDDs corresponded to between one (Carman 2016) and three (Carman 2017) soybean developmental stages at both AYL levels. Studies in other regions have found similar results (Hock et al 2006;Nice et al 2001;Rasool et al 2017), as wide-row spacing extends the period of light penetration into the canopy (Puricelli et al 2003;Steckel and Sprague 2004). In this experiment, the canopy did not close completely in the widerow treatments at any of the site-years (data not shown).…”
Section: Row-spacing Experimentssupporting
confidence: 77%
“…This range of GDDs corresponded to between one (Carman 2016) and three (Carman 2017) soybean developmental stages at both AYL levels. Studies in other regions have found similar results (Hock et al 2006;Nice et al 2001;Rasool et al 2017), as wide-row spacing extends the period of light penetration into the canopy (Puricelli et al 2003;Steckel and Sprague 2004). In this experiment, the canopy did not close completely in the widerow treatments at any of the site-years (data not shown).…”
Section: Row-spacing Experimentssupporting
confidence: 77%
“…However, the extent of competition depends on weed density (Dunan et al 1995), weed type, and weed species (Marshall et al 2003). Weed emergence time (Dieleman et al 1996), growth habit, and duration of the competition (Rasool et al 2017;Swanton et al 2015) influenced the extent of weed-crop competition. Characteristics like tall height (100 to 200 cm tall) and long emergence time of feather fingergrass enable this weed to become competitive, causing substantial seed production (GRDC 2014;Ngo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…System intensification attempts to increase light penetration through improved crop canopy coverage while minimizing interspecific competition by limiting weed growth [6][7][8]. As a result, soybean planted at closer spacing performs better than crop sown at broader spacing [9,10].…”
Section: Introductionmentioning
confidence: 99%